The Best Job in the Joint. - Faulkner, Clarence (Raven Chronicles, 2006)
The article focuses on the author's experience inside a prison in Texas. He was sentenced to 25 years in the Texas Department of Corrections for robbing the Inn of the Golden West in Odessa, Texas. His experience in COBOL and Fortran computer programming led him to a work in another unit with easier life and better accommodation.